A Simulation Study of Magnesium Alloy AZ31B Behavior in High-Velocity Impact and Ballistic Limit - Mohamad Fariz, Mohamed Nasir*; Mohamad Faizal, Abdullah; Muhammad Naim Rabbani, Kamarulzaman; Muhammad Izzat Nor, Ma'arof; Girma, Tadesse Chala (INTI International University, 2022)
Magnesium Alloy are made of magnesium combined with different metal elements to improve the physical properties. The elements included were manganese, aluminium, zinc, silicon, copper, zirconium, and rare-earth metals. The magnesium density has been stated to be significantly 35% less than aluminium and significantly 77% less than steel. Many technologies nowadays required materials that are high strength but lightweight. Alloys based on magnesium are current interest to the military nation of the UnitedStates due to they are considered as the lightest structural metal alloys. There are fewer studies to observe the relationship between magnesium alloys and impact loading compared to several traditional materials, such as steel, under ballistic condition. The objective of this study to observe the behaviour and the mechanical properties of the Magnesium alloy AZ31B under ballistic impact test. The computational simulation using Ansys found based on the result obtained, the ballistic limit of the Magnesium alloy AZ31B when being impacted by 5.56 x 45 mm NATO projectile is 775 m/s whereas, when being impacted by the 7.62 x 39mm, the ballistic limit is 645 m/s. Hence, complete penetration can be seen on the specimen when it reached the ballistic limit stated.